2017
DOI: 10.16984/saufenbilder.283221
|View full text |Cite
|
Sign up to set email alerts
|

Gıda Makineleri Endüstrisinde Akış Odaklı Tesis Yerleşimi Uygulaması

Abstract: İşletmeler, küresel dünyanın katı rekabet ortamına uyum sağlayabilmek ve ayakta kalabilmek için kârlılıklarını arttırmak zorundadırlar. Karlılığı arttırmanın akla gelen ilk uygulaması ürün fiyatlarının arttırılması düşüncesidir. Ancak uzun vadede beklenen kalite düzeyine eşlik eden fiyat müşteri için belirleyicidir. Bu zorlayıcı fiyat faktörü nedeni ile işletmeler öncelikle metot etüdü, kaizen gibi çalışmalarla sürekli olarak süreci optimize ederek maliyeti düşürme yollarını tercih etmektedirler. Sürecin optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Deste and İlhan Küçük (2021) examined the operation of a machine used in sheet cutting within the scope of work study techniques, identified inefficiencies, and stated how the design of the new machine should be. Akbilek (2017) developed a new layout plan with existing equipment to increase productivity in a food machine production facility in line with the increasing demand and customer expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Deste and İlhan Küçük (2021) examined the operation of a machine used in sheet cutting within the scope of work study techniques, identified inefficiencies, and stated how the design of the new machine should be. Akbilek (2017) developed a new layout plan with existing equipment to increase productivity in a food machine production facility in line with the increasing demand and customer expectations.…”
Section: Introductionmentioning
confidence: 99%